LEGAL PROTECTION EFFORTS FOR MSME ENTREPRENEURS BASED ON LAW NO. 11 OF 2020 ON JOB CREATION LAW - Suprapti, Duhita Driyah; Ristanti, Dina; Pangestika, Finna Maessy; Fuad, Choirul; Alfarisi, Salman (Indonesia Law Review, 2025)
Indonesia is the fourth-highest country with a level of population density that will undoubtedly cause many problems, one of which is the problem related to unemployment that is increasingly increasing. Therefore, the Government then took the initiative to issue a law that can pioneer job creation, ease of effort, investment, and empowerment of small micro-businesses. Focus on the actions of youth in making investments then whether this Job Creation Law also provides adequate protection for entrepreneurs, especially MSME entrepreneurs. MSME entrepreneurs need legal protection because most do not understand the Law in Indonesia and cannot afford to hire legal counsel or lawyers. The protection guaranteed by the Government makes MSME actors immensely helped. This research seeks to examine the application of Job Creation Law to Micro Small, Medium Enterprises (MSMEs). So that it is expected to make a positive contribution in formulating a system of legal protection that is in accordance and sustainable in harmony with the Business, Micro, Small, Medium Law (MSMEs) as well as laws related to investment and the 1945 Constitution as the basis of the Indonesian state, the research will be conducted with field research into locations that the author considers relevant to the issues raised. Such an approach is expected to support the validity of the study results as sound output. Protection for MSMEs along with increasing investment. On the other hand, the Tegal Regency Government has implemented several measures. The Tegal Regency Government is assisted by the DPMPTSP, the Industry and Manpower Service, and the Trade, Cooperatives, and MSMEs Service to help each other provide guidance related to business legality. These agencies also have internal efforts to help each other manage business legality in Tegal Regency. According to Shinta, as the owner of the Bolen Nyempluk business, it is pretty easy, one of which is for PIRT permits for food businesses that can be accessed by the Disperindagkop which collaborates with the DPMPTSP, even for product packaging, recommendations, and provisions are also provided by the Disperindagkop. In providing assistance and legal assistance services, PP No. 7 of 2021 also states that in certain emergency conditions, the Central and Regional Governments must seek MSME recovery by doing several things such as credit restructuring, business reconstruction, financial assistance, and providing services in other forms. In addition, Article 54 of Government Regulation Number 7 of 2021 also mandates that the Central and Regional Governments play an active role in providing protection and security to maintain the competitiveness of MSME products in the domestic market. To increase product competitiveness, the Ministry of Industry and Manpower also includes training and coaching to business actors, and this training activity also involves business actors and prospective business actors. Providing access to this license certainly makes people interested in having their own business because the licensing process is more straightforward, but they still get coaching.